Characterization and Management of Arrhythmic Events in Young Patients With Brugada Syndrome - Michowitz, Yoav; Milman, Anat; Andorin, Antoine; Sarquella-Brugada, Georgia; Gonzalez Corcia, M. Cecilia; Gourraud, Jean-Baptiste; Conte, Giulio; Sacher, Frederic; Juang, Jimmy J.M.; Kim, Sung-Hwan; Leshem, Eran; Mabo, Philippe; et al. (Journal of the American College of Cardiology, 2019)
Information on young patients with Brugada syndrome (BrS) and arrhythmic events (AEs) is limited. The purpose of this study was to describe their characteristics and management as well as risk factors for AE recurrence. A total of 57 patients (age ≤20 years), all with BrS and AEs, were divided into pediatric (age ≤12 years; n = 26) and adolescents (age 13 to 20 years; n = 31). Patients’ median age at time of first AE was 14 years, with a majority of males (74%), Caucasians (70%), and probands (79%) who presented as aborted cardiac arrest (84%). A significant proportion of patients (28%) exhibited fever-related AE. Family history of sudden cardiac death (SCD), prior syncope, spontaneous type 1 Brugada electrocardiogram (ECG), inducible ventricular fibrillation at electrophysiological study, and SCN5A mutations were present in 26%, 49%, 65%, 28%, and 58% of patients, respectively. The pediatric group differed from the adolescents, with a greater proportion of females, Caucasians, fever-related AEs, and spontaneous type-1 ECG. During follow-up, 68% of pediatric and 64% of adolescents had recurrent AE, with median time of 9.9 and 27.0 months, respectively. Approximately one-third of recurrent AEs occurred on quinidine therapy, and among the pediatric group, 60% of recurrent AEs were fever-related. Risk factors for recurrent AE included sinus node dysfunction, atrial arrhythmias, intraventricular conduction delay, or large S-wave on ECG lead I in the pediatric group and the presence of SCN5A mutation among adolescents. Young BrS patients with AE represent a very arrhythmogenic group. Current management after first arrhythmia episode is associated with high recurrence rate. Alternative therapies, besides defibrillator implantation, should be considered. [Display omitted]